GC-MS Profiling and Literature-Based Mechanistic Prediction of Lemon Essential Oil and Mango Leaf Extract as Potential Supportive Candidates for Nicotine Addiction Management - Sulistiyaningsih, Sulistiyaningsih; Rini, Tri Diana Puspita; Anggraeni, Indiana Gita (Sciences of Pharmacy, 2026)
Nicotine addiction remains a major global health problem that necessitates the development of safe and effective supportive therapies. This study aimed to characterize the metabolite profiles of lemon essential oil (Citrus limon (L.) Burm. f.) and 96% ethanol extract of mango leaves (Mangifera indica L.) using Gas Chromatography–Mass Spectrometry (GC-MS) and to explore their potential mechanisms in nicotine addiction management through a literature-based mechanism mapping approach. Compounds were identified based on retention time, mass spectrum matching, and relative peak area percentages. GC-MS analysis showed that lemon essential oil was predominantly composed of D-limonene (58.72%), followed by β-pinene (13.82%) and γ-terpinene (11.43%). Meanwhile, the 96% ethanol extract of mango leaves was dominated by methyl gallate (27.61%), along with several phenolic compounds and triterpenoids, including vitamin E and lupeol. The identified metabolites suggest distinct but potentially complementary biological activities. Lemon essential oil may exert supportive effects through neuromodulatory pathways, whereas mango leaf extract may contribute through antioxidant and anti-inflammatory mechanisms. These findings indicate that both natural products possess potential complementary roles as supportive agents in nicotine addiction management. However, further biological and clinical studies are required to validate their efficacy and safety.